Experimental studies and constitutive modelling of AA6082 in stress-relaxation age forming conditions. (2017) - Rong, Q.; Shi, Z.; Li, X.; Sun, X.; Li, Y.; Yang, Y.-L.; Meng, L.; Lin, J.
Abstract: AA6082 is a popular material for automotive body structure because of its good formability and weldability. In this study, stress relaxation and ageing behaviour of AA6082 at T6 condition were investigated through stress relaxation tests with three different initial stresses at 160 °C for 12 h. Interrupted tests for 1, 3, 5 and 12 h and subsequent uniaxial tensile tests were carried out to investigate the effect of ageing time on yield strength of the material. The results show that after 12 h stress relaxation tests with initial stresses of 173, 198, and 225 MPa, the stresses relaxed were respectively 19.4 %, 24.3 %, and 25.6 % of the initial stresses. Minor change of yield strength of the material throughout the ageing time was observed. Moreover, a set of unified constitutive equations was calibrated to model the stress relaxation behaviour of AA6082 during creep age forming process, and related material constants for the AA6082 were determined. A close agreement between experimental data and computed results has been achieved for stress relaxation behaviour of the material. This study helps to understand the stress relaxation behaviors of AA6082 material, and facilitates the CAF applications of AA6082 material in industrial field.